Bayesian inference for latent factor copulas and application to financial risk forecasting - Benedikt Schamberger; Lutz F. Gruber; Claudia Czado (Econometrics, 2017)
Factor modeling is a popular strategy to induce sparsity in multivariate models as they scale to higher dimensions. We develop Bayesian inference for a recently proposed latent factor copula model, which utilizes a pair copula construction to couple the variables with the latent factor. We use adaptive rejection Metropolis sampling (ARMS) within Gibbs sampling for posterior simulation: Gibbs sampling enables application to Bayesian problems, while ARMS is an adaptive strategy that replaces traditional Metropolis-Hastings updates, which typically require careful tuning. Our simulation study shows favorable performance of our proposed approach both in terms of sampling efficiency and accuracy. We provide an extensive application example using historical data on European financial stocks that forecasts portfolio Value at Risk (VaR) and Expected Shortfall (ES).
Keywords: C11; C31; C38; C51; C58; C63; 330; Bayesian inference; dependence modeling; factor copulas; factor models; factor analysis; latent variables; MCMC; portfolio risk; value at risk; expected shortfall